Real Options Valuation : an application to the portuguese real estate market - Oliveira, Carla (2018)
The contribution of real options analysis on the valuation of Portuguese undeveloped building sites is significant on the decision making regarding the apartment-buildings construction. Using the options model developed by Quigg (1993), and including the necessary readjustments for the Portuguese market, it was found that the scale price elasticity parameter and construction expenditures’ elasticity of scale parameter had a strong impact on building sites’ values. The empirical analysis revealed that the option to defer adds value to undeveloped building sites’ valuations. This fact cannot be ignored when deciding upon an investment’s implementation.